Increased levels of anti‐non‐Gal IgG following pig‐to‐baboon bone marrow transplantation correlate with failure of engraftment. (29th October 2013) - Liang, Fan; Wamala, Isaac; Scalea, Joseph; Tena, Aseda; Cormack, Taylor; Pratts, Shannon; Duran‐Struuck, Raimon; Elias, Nahel; Hertl, Martin; Huang, Christene A.; Sachs, David H.
Abstract Background The development of genetically modified pigs, which lack the expression of alpha 1‐3 galactosyl transferase, (GalT‐KO pigs) has facilitated the xenogeneic transplantation of porcine organs and tissues into primates by avoiding hyperacute rejection due to pre‐existing antibodies against the Gal epitope. However, antibodies against other antigens (anti‐non‐Gal antibodies), are found at varying levels in the pre‐transplant sera of most primates. We have previously found that baboons with high levels of pre‐transplant anti‐non‐Gal IgG, conditioned with a non‐myeloablative conditioning regimen, failed to engraft following pig‐to‐baboon bone marrow transplantation (Xenotransplantation, 17, 2010 and 300). Two baboons with low levels of pre‐transplant anti‐non‐Gal IgG, conditioned with the same regimen, showed porcine bone marrow progenitors at 28 days following transplantation, suggesting engraftment. These baboons also showed evidence of donor‐specific hyporesponsiveness. This observation led us to investigate the hypothesis that selecting for baboon recipients with low pre‐transplant anti‐non‐Gal IgG levels might improve engraftment levels following GalT‐KO pig‐to‐baboon bone marrow transplantation. Methods Five baboons, with low pre‐transplant anti‐non‐Gal IgG levels, received transplantation of bone marrow cells (1–5 × 109/kg of recipient weight) from GalT‐KO pigs. They received a non‐myeloablative conditioning regimen consisting of low‐dose total body irradiation (TBI) (150 cGy), thymic irradiation (700 cGy), anti‐thymocyte globulin (ATG), and tacrolimus. In addition, two baboons received Rituximab and Bortezomib (Velcade) treatment as well as extra‐corporeal immunoadsorption using GalT‐KO pig livers. Bone marrow engraftment was assessed by porcine‐specific PCR on colony forming units (CFU) of day 28 bone marrow aspirates. Anti‐non‐Gal antibody levels were assessed by serum binding toward GalT‐KO PBMC using flow cytometry (FACS). Peripheral macro‐chimerism was measured by FACS using pig and baboon‐specific antibodies and baboon anti‐pig cellular responses were assessed by mixed lymphocyte reactions (MLR). Results As previously reported, two of five baboons demonstrated detectable bone marrow engraftment at 4 weeks after transplantation. Engraftment was associated with lack of an increase in anti‐non‐Gal IgG levels as well as cellular hyporesponsiveness toward pig. Three subsequent baboons with similarly low levels of pre‐existing anti‐non‐Gal IgG showed no engraftment and an increase in anti‐non‐Gal IgG antibody levels following transplantation. Peripheral macrochimerism was only seen for a few days following transplantation regardless of antibody development. Conclusions Selecting for baboon recipients with low levels of pre‐transplant anti‐non‐Gal IgG did not ensure bone marrow engraftment. Failure to engraft was associated with an increase in anti‐non‐Gal IgG levels following transplantation. These results suggest that anti‐non‐Gal‐IgG is likely involved in early bone marrow rejection and that successful strategies for combating anti‐non‐Gal IgG development may allow better engraftment. Since engraftment was only low and transient regardless of antibody development, innate immune, or species compatibility mechanisms will likely also need to be addressed to achieve long term engraftment.